Life Threatening: The Most Important Concern of Patients Confronting Cancer Diagnosis - Ravanbakhsh Esmaeili; Fazlollah Ahmadi; Eesa Mohammadi; Abdolhakim Tirgari Seraj (Tehran University of Medical Sciences, 2013)
Background & Aim: Increase in cancer prevalence results in feeling fear of being diagnosed with cancer among individuals. Understanding concerns of patients diagnosed with cancer helps health care professionals to provide appropriate caring plans. This study aimed to understand main concerns of patients who confront cancer diagnosis. Methods & Materials: This was a qualitative study with content analysis approach. Fifteen patients with cancer were selected from a specialized hospital, an oncology clinic, and Emdad Center of Cancer patients in Sari using a purposeful sampling method during May 2011 to June 2012. The sample size was completed regarding data saturation. Data were collected using interviews, observations and recording field notes. All interviews were tape-recorded and transcribed verbatim. Data were analyzed using descriptive content analysis and the Granhim and Landmann method. Results: Three categories including 485 primary codes were emerged. The derived codes were as follows: 1) sever personal and family disturbance 2) imagination of despair and 3) unclear imagination of future. The main code included in all derived codes was life threatening nature of cancer. Conclusion: The findings showed that life threatening nature of cancer is a source of fear that makes the disease frightening. Clinical staff and nurses should pay more attention to concerns of patients with cancer and design their care plan accordingly.